Association of Chlamydia pneumoniae IgG and IgA antibody in coronary artery disease - Swetha, M.; Sadananda, K. S.; Venkatesha, D.; Anuradha, K. (International Journal of Research in Medical Sciences, 2017)
Background:Cardiovascular disease, resulting from atherosclerosis, is a leading cause of global morbidity and mortality. Classical risk factors explain much of the attributable risk for cardiovascular events, but other risk factors for the development and progression of atherosclerosis, which can be identified, may be important therapeutic targets. Infectious agents, such as Chlamydia pneumoniae, have been proposed as contributory factors in the pathogenesis of atherosclerosis. The present study was conducted to determine the seroprevalence of C. pneumoniae antibodies and to study the association of chronic C. pneumoniae infection with Coronary Artery Disease (CAD). Methods:The study group included 90 angiographically proven CAD patients and age and sex matched 90 normal coronaries as control group. With total aseptic precaution 3 ml blood was collected. Enzyme linked immunosorbant assay was performed for all subjects to detect the presence of IgG and IgA antibodies to Chlamydia pneumoniae (Cp). Results:IgG and IgA Cp antibodies were detected in 67.8% and 58.9% CAD patients compared to 45.6% and 11.1% controls. IgG + IgA Cp antibodies were detected in 88.9% CAD patients when compared to 50.0% controls. Seroprevalence of IgG and IgA Cp antibodies were high among CAD patients compared to controls and was found statistically significant. A significant presence of Chlamydia pneumoniae antibodies was detected in smokers, diabetes mellitus, hypertension, and dyslipidemia. Conclusion:In the present study, the seroprevalence of IgG and IgA Cp antibodies was found to be higher in CAD patients compared to controls. The present study supports the association between Chlamydia pneumoniae infection and Coronary artery disease.